Les « leçons d’histoire » revues et corrigées par le théâtre jeunes publics contemporain - Marie Sorel (Amnis)
Contemporary theatre for young audiences, still relatively rare in class, is reluctant to give its recipients history lessons in due form. Concerned about freeing itself from the legacy of « educational theatre », didactic and moralising, the authors willingly cultivate a casual, non-educational stance, turning a priori more toward the here-and-now and the mundane rather than toward the past. But history, particularly its painful episodes –the two World Wars, the Holocaust, the Occupation, colonization– appears often, if only by allusion, on the young audience stage. This article addresses the alternative route taken by the authors of theatre for young audiences –Joseph Danan, Françoise Du Chaxel, Jean-Claude Grumberg, Joël Jouanneau, David Lescot, Sylvain Levey, Naomi Wallace– to educate young readers about the past as well as to the narrative of the past, in particular to its silences and its biases. The rewriting of tales and Robinsonade stories, the proliferation of narrative and retrospective voices, humour and fantasy are among the techniques applied by this reflective and hybrid theatre to question the modalities of writing history. Conscious of the limits of the vertical and intergenerational model of the transmission of the past, the authors tap into the imagination and critical thinking of young readers to question how impervious the partitions are between the past and the present, reality and fiction, history recorded and recounted.